The determination of antioxidant and lead content of hemiparasite Dendrophthoe vitellina (F. Muell) Tiegh on Nutmeg - Sabandar, Anna Helena; Kasmiyati, Sri; Djohan, Djohan (Universitas Ahmad Dahlan, 2023)
Mistletoe, a parasitic plant growing on nutmeg trees, is conventionally perceived as a parasitic entity with limited regard for its potential medicinal value. On the other hand, mistletoe has a remarkable potential source of valuable medicinal compounds, particularly in traditional healthcare, due to its secondary metabolites such as flavonoid, phenolic, ascorbic acid, and antioxidant activity. Nevertheless, both the host tree and the environment, like Pb, influence the adaptive responses of secondary metabolites. This study aimed to determine the secondary metabolites, such as flavonoids, phenolics, ascorbic acid, antioxidant activity, and Pb content in the leaves of D. vitellina and nutmeg (M. fragrans). The samples were obtained via maceration using ethanol. The spectrophotometric analysis method was used to measure several parameters, using particular reagents for phenolic compounds using Folin-Ciocalteu, flavonoids using AlCl3, and ascorbic acid using sulfosalicylic acid), antioxidant activity using DPPH, and Pb using the AAS method. The results indicated that D. vitellina possesses a higher concentration of flavonoid and phenolic compounds, followed by 3.36 ± 1.92 % (w/w) and 18.45 ± 2.35 % (w/w) respectively. Conversely, nutmeg had a significant ascorbic acid concentration of 3.99 ± 4.38 % (w/w). The significant presence of phenolics and flavonoids had a crucial role in the antioxidant activity seen in D. vitellina, which exhibited exceptionally potent antioxidant properties. All samples contain Pb, ranging from 0.00001–0.00021 % (w/w), within the maximum allowable limits. Therefore, mistletoe is notable for being a reliable and encouraging plant species that can provide a natural supply of antioxidants and be safely used in traditional medicine.